Monarch’s Titles in Mediaeval Serbia - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Stefan Nemanja, the founder of Serbian dynasty, carried the title of the Great Župan. In 1217 Nemanja’s son Stefan got the royal crown from the Pope Honorius the Third and the title of King was carried by Serbian monarchs till 1346, when Stefan Dušan took the title of Emperor (Tsar). Though the Serbian Empire did not last very long, it happened that after Dušan’s death two rulers carried the title of Tsar: Dušan’s son and legitimate successor Uroš (since 1355) and Dušan’s half brother Simon-Siniša, lord of Thessaly and Epiros (since 1356). After 1371 the title of Serbian monarch was Knez (Prince) and since 1402 till 1459 Despot. Besides the monarch’s title the territory that he ruled over was always designated. Territorial formula had partly permanent, partly variable content. Usually the Serbian rulers, since Stefan the First-Crowned, called themselfs Serbian King or King of whole Serbian Land. Later on, after proclamation of the Empire, in charters written in Serbian language the signature was Tsar of Serbs and Greeks. However, in documents written in Greek language, there is the permanent formula of Dušan’s signature: Emperor and Autocrat of Serbia and Romania.Territorial formula of monarch’s title in mediaeval Serbia had some variable ingredients as well, which sometimes appeared and sometimes disappeared. The author mentioned all cases that he could find in the legal sources.